Analisis Pengalaman Pelanggan terhadap Layanan di Bengkel Motor F21 Sinergy - Muhammad Ibni Fauzan (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyze customer experience with the services provided by F21 Sinergy Motorcycle Workshop. The method used is a qualitative approach with data collection techniques in the form of in-depth interviews and participatory observations of 12 customers who have used the workshop's services more than once. The main focus of this study is to understand customer perceptions of service quality, speed of repair, technician professionalism, and overall satisfaction with the results of motorcycle repairs.